If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + (2x + -12) = 42 Reorder the terms: 4x + (-12 + 2x) = 42 Remove parenthesis around (-12 + 2x) 4x + -12 + 2x = 42 Reorder the terms: -12 + 4x + 2x = 42 Combine like terms: 4x + 2x = 6x -12 + 6x = 42 Solving -12 + 6x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6x = 42 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 42 + 12 6x = 42 + 12 Combine like terms: 42 + 12 = 54 6x = 54 Divide each side by '6'. x = 9 Simplifying x = 9
| 2-(3x+1)+6=15 | | 9x*9=15 | | sin(5x)-sin(3x)=cos(4x) | | -64x^2+16=0 | | n^2+9n+28=0 | | 0.4*7/3*8/15 | | n+9n+28=0 | | 0.4*7/3 | | 8x-4=4x+16 | | (27m^5-16m^2)/3m | | 6u+42=-3(u+7) | | 2/6x4 | | 7p+9=-9(p-3) | | x=3929.25-3665 | | 2x+2=2(2-x)+6 | | 2.75x+35=2.45x+95 | | 0.0977=ln(x) | | (x+6)(2x-5)+(x+6)(x+9)=0 | | 3.35x=2.75x+35 | | 10x-4+2x=-24 | | -x^2+2x+4= | | 5a+4b=10 | | 16=6x+x^2 | | 3(2n+1)=9 | | 0=y^2+5y-36 | | 84=x/6 | | 11=6+1.2(x-6) | | ((X^-1/2)(x^5/2))/(x^1/3) | | U=2(9n+35)+7(n+1) | | ((8b^5c^2)/(15c))x(3c/2b) | | -34+u=-16 | | 5=1.2(x-7) |